An acceptable time - L'Engle, Madeleine (L'Engle, Madeleine. Time quintet, 2007)
Polly's visit to her grandparents in Connecticut becomes an extraordinary experience as she encounters old friends and mysterious stangers and finds herself traveling back in time to play a crucial role in a prehistoric confrontation.